(untitled) (Research, Society and Development, 2021)
Type 2 diabetes mellitus (DM) develops due to peripheral insulin resistance, tied to secretory pancreatic fatigue, its pathophysiology involves genetic and environmental factors, such as poor diet and sedentary lifestyle. Diabetic patients have a risk factor for the development of microvascular lesions, such as retinopathy, neuropathy, nephropathy. To evaluate how GLP-1 receptor agonists act as a protective factor for chronic kidney disease in patients with type 2 diabetes mellitus. For the survey of articles in the literature, searches were conducted in the following databases: Latin American and Caribbean Literature in Health Sciences (LILACS), Medical Literature Analysis and Retrieval Sistem online (Medline), Scielo, and articles published in the period 2016-2021, in Portuguese, English and Spanish. From the studies, it was possible to perceive the intimate relationship between patients with type 2 DM and chronic kidney disease (CKD) and the nephroprotective function of GLP-1 analogues. As the development of microvascular lesions is usually chronic and silent, these patients should be monitored frequently. For patients with high chances of kidney injury, the use of GLP-1 analogues has been shown to be a great choice, because in addition to hypoglycemic agents they still have nephroprotective factor, through the reduction of the release of cytokines and hormones capable of directly harming renal cells.